At 28 GHz microstrip patch antenna for wireless applications: a review - Md. Sohel Rana; Piyal Mistry; Md. Jahidur Rahaman; Sahriar Islam Shipon; Shake Zion Haider Ovi; Md. Masud Rana; Tahasin Ahmed Fahim (Universitas Ahmad Dahlan, 2024)
Microstrip patch antennas are becoming increasingly popular because they are small, have low profiles, are easy to integrate, are very cheap, and work well. For this reason, this antenna could be used for wireless communication systems. This research paper reviews and studies 28 GHz microstrip patch antenna for wireless applications. Different substrate materials have been used to make these antennas, such as FR-4 (loss), FR-4 Epoxy, Rogers RT/droid 5880, TLC-30, Rogers RT/droid 5880 LZ, and others. Different substrate materials and shapes were used to make microstrip patch antennas with a frequency of 28 GHz. This article discusses the different sizes of antennas, the other geometric shapes antennas can take, the different ways antennas’ properties can be analyzed, and the different types of antennas. It will also talk about the material, thickness, loss tangent, return loss, bandwidth, voltage standing wave ratio (VSWR), gain, efficiency, and directivity of the substrate. This antenna is used for super-high-frequency (SHF), radars, commercial wireless local area networks (LANs), cell phones, and other wireless communications systems.